ANALISIS TINGKAT RISIKO TSUNAMI TERHADAP BANGUNAN HUNIAN DI DESA ULEE LHEUE KECAMATAN MEURAXA KOTA BANDA ACEH - Isnin, Siti Nidia (Jurnal Ilmiah Ilmu Sosial, 2016)
On 26th of December 2004, a giant wave ‘Tsunami’ triggered by enourmous earthquake of 9 richter scale in magnitude located in Indian Ocean, to the west of Sumatra Island. This study is focusing on‘ Tsunami Risk Level on Residential Buildings in Ulee Lheue Village, Meuraxa Sub-district, Banda Aceh’. This study is aiming to determine the level of the Tsunami potential danger, to determine the level of vulnerability of the Tsunami on Residential Buildings and to determine the level of the Tsunami risk on residential buildings. Determining the level of the Tsunami potential danger is based on coastal line inundation modelling which are 1 m, 2 m, 5 m, 15 m and 30 m. This study considered the residential buildings as element at risk. The level of Tsunami vulnerability on residential buildings is based on relative vulnerbility index (RVI) of PTVA-3 model and its modifications. The level of the Tsunami risk on residential buildings is based on risk classes. Tsunami risk classes on residential buildings using PTVA model are not different with modification model. Inundation scenario of 1 m, 2 m, and 5 m, tsunami risk class on residential building is catogorized into Class I and inundation scenario of 15 m and 30 m is categorized into class II. The differance of the models is lied on the nominal of potential loss. Keyword: Risk, Tsunami, Residential Buidlings, Ule Lheue Village